The age‐related obesity paradigm: results from two large prospective cohort studies - Yi‐Zhong Ge; Tong Liu; Li Deng; Qi Zhang; Chen‐An Liu; Guo‐Tian Ruan; Hai‐Lun Xie; Meng‐Meng Song; Shi‐Qi Lin; Qin‐Hua Yao; Xian Shen; Han‐Ping Shi; et al. (Wiley, 2024)
Abstract Background The obesity paradigm has been a health concern globally for many years, its meaning is controversial. In this study, we assess the characteristics and causes of obesity paradigm and detail the mediation of obesity and inflammation on survival. Methods The original cohort included participants from the US National Health and Nutrition Examination Survey (NHANES) from 1999 to 2018, a prospective cohort of a nationally representative sample of adult participants; the oncology validation cohort included patients from the Investigation on Nutrition Status and Clinical Outcome of Common Cancers (INSCOC) from 2013 to 2021, a prospective cohort of Chinese patients with cancer. Survival analysis was performed using weighted (NHANES) or unweighted (INSCOC) Cox survival analyses. The normal BMI group was used as a reference for all comparisons. Systemic inflammation was defined as neutrophil‐to‐lymphocyte ratio (NLR) > 3. Model‐based causal mediation analysis was used to identify the mediators. Results A total of 52 270 (weighted population: 528506229) participants of the NHANES [mean follow‐up times: 10.2 years; mean age (SD): 47 (19.16) years] were included in the original cohort; and a total of 17 418 patients with cancer of INSCOC [mean follow‐up times: 2.9 years; mean age (SD): 57.37 (11.66) years] were included in the validation cohort. In the subgroups of all the participants, the obesity paradigm was more apparent in older participants and participants with disease [HR (95% CI): age ≥ 65 years, 0.84 (0.76, 0.93); with cancer, 0.84 (0.71, 0.99); with CVD, 0.74 (0.65, 0.85)]. As aged, the protective effect of a high BMI on survival gradually increased and a high BMI showed the effect of a protective factor on older participants [for obese II, HR (95% CI): young adults, 1.91 (1.40, 2.62); middle age, 1.56 (1.28, 1.91); old adults, 0.85 (0.76, 0.96]). The aged‐related obesity paradigm in patients with cancer from the NHANES was verified in the INSCOC cohorts [for obese, HR (95%CI): 0.65 (0.52, 0.81)]. The NLR is an important mediator of the effect of BMI on survival (proportion of mediation = 15.4%). Conclusions The obesity paradigm has a strong correlation with age. Relative to normal weight, obese in young people was association with higher all‐cause mortality, and obese in elderly people was not association with higher mortality. The protection of obesity is association with systemic inflammation.